Solvatofluorochromism of Conjugated 4-Methoxyphenyl-Pyridinium Electron Donor-Acceptor Pairs - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M; Pastenes, C (Elsevier Ltd, 2019)
Four new fluorescent dyes, composed of a 4-methoxyphenyl-pyridinium electron donor-acceptor pair, were synthesized and their solvatofluorochromism was investigated in thirteen different solvents with a wide range of polarities. Their different solvatofluorochromism behavior was rationalized by consideration of the relative regioisomeric conjugation of the donor and acceptor groups, the presence of a phenyl spacer between the donor and acceptor rings, and the increased rigidity and planarity of an analogous tetrahydrodibenzacridinium acceptor system. Their behavior was further rationalized by theoretical calculations of the absorption and emission processes for the four dyes dissolved in dichloromethane. © 2019 Elsevier Ltd
Keywords: Pyridinium dyes; Solvatochromism; Solvatofluorochromism; Excited states; TDDFT calculations